Capaian Tujuan Pembangunan Berkelanjutan Kota Samarinda Sebagai Bahan Evaluasi Kinerja Pembangunan Hijau - Rustam; Muhammad Jalaluddin; Yohanes Budi Sulistioadi; Nadya Tursina; Siti Nurhasanah (Fakultas Kehutanan dan Lingkungan Tropis, Universitas Mulawarman, 2023)
The Sustainable Development Goals (SDGs) are a new direction to achieve green development in social, economic, environmental, and governance development. This study is a collaboration activity of the Geospatial Information Infrastructure Development Center (PPIIG) SDGs Center of the Research and Services Institute (LP2M) of Mulawarman University and Regional Planning and Development Agency of Samarinda City. The purpose of this study is to identify and analyze the achievement of the Samarinda City SDGs is based on the national targets and indicators. The method used is a desk study and focus group discussion based on available data and then analyzed based on the matching and vulnerability of city level of SDGs indicators and targets. The results showed that there are 100 indicators and 15 targets that are under the authority of the City Government of Samarinda. The result of this study is the SDGs indicator have been implemented and achieved on the national target in 42%, 16 % have been implemented but it’s not been achieved on the national target yet, 2 % of indicator is not been implemented, and 40% of indicator is no data. The government of Samarinda focus on poverty, health, cities and settlement, education, fresh water, infrastructure, and governance to achieve the targets as tools to evaluating and improving their performance. There are gaps and challenges to improving and implementation the indicators, especially on data availability and awareness of government apparatus. Stakeholders’ collaboration is deeply needed to achieve SDGs national targets and integrated to the Samarinda development planning.